2010
DOI: 10.1128/aem.00182-10
|View full text |Cite
|
Sign up to set email alerts
|

Verotoxin 2 Enhances Adherence of Enterohemorrhagic Escherichia coli O157:H7 to Intestinal Epithelial Cells and Expression of β1-Integrin by IPEC-J2 Cells

Abstract: Verotoxin (VT) has been implicated in the promotion of adherence to and colonization of intestinal epithelial cells by enterohemorrhagic Escherichia coli (EHEC) O157:H7. The present study investigated the effect of VT2 on the adherence of EHEC O157:H7 strain 86-24 to porcine jejunal (IPEC-J2), human colon (CaCo-2), and human laryngeal carcinoma (HEp-2) cell lines and on the expression in IPEC-J2 cells of synthases for ␤1-integrin and nucleolin, both of which are implicated in bacterial adherence. The effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Recent studies using in vitro cell culture and mouse models suggest that besides inducing systemic disease, Stx2 production can also promote the colonization of epithelial cells by enhancing the expression of host cell intimin receptors (40,57). In contrast to this, similar studies conducted in cattle and rabbits suggested no effect of Stx on colonization on intestine (55,61).…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies using in vitro cell culture and mouse models suggest that besides inducing systemic disease, Stx2 production can also promote the colonization of epithelial cells by enhancing the expression of host cell intimin receptors (40,57). In contrast to this, similar studies conducted in cattle and rabbits suggested no effect of Stx on colonization on intestine (55,61).…”
Section: Discussionmentioning
confidence: 57%
“…Not much is known about expression of ␤ 1 -integrin receptors in porcine tissues. However, some evidence has shown that ␤ 1 -integrins are expressed in the porcine intestine and in isolated intestinal epithelial cells of swine (47,48). Efficient invasin-mediated engagement of ␤ 1 -integrin receptors in the intestine could inhibit spread to other host sites and enable the pathogen to remain in the intestine of the pigs for extended time periods.…”
Section: Discussionmentioning
confidence: 99%
“…As one study demonstrates, Shiga toxins may act as a bacterial defense against Eukaryotic predators (Lainhart et al 2009). Shiga toxins have also been implicated in the promotion of adherence and colonization of O157:H7 to human intestinal epithelial cells in comparison to stx-negative strains (Liu et al 2010). However, selective advantages are more likely to operate in the bovine reservoir or external environment than in the human gastrointestinal tract as they are considered "accidental hosts," and STEC/enterohemorrhagic E. coli (EHEC) are unlikely to have evolved specifically to cause human infection (Franz et al 2014).…”
Section: Conrad Et Almentioning
confidence: 99%